2012
DOI: 10.3109/01612840.2011.653036
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Depressive Symptoms and Drinking Patterns in First Year College Students

Abstract: Depression and alcohol use are often found in college students, particularly during their first year. The current study assessed the interrelationship of alcohol use and specific depression symptoms. A large sample (n = 869) of first year students were invited to participate via the Internet Results indicated that specific depression symptoms correlated with alcohol consumption. Self-reported heavy, problem drinkers experienced significantly higher Beck Depression Inventory scores than all other groups. Our fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 50 publications
7
43
1
1
Order By: Relevance
“…The study of Geisner (20) confirms this and indicates that non-drinking students reported more depressive symptoms than drinking students. They state that drinking could be a strategy to cope with the experienced demands or a reason for enhancing social activities.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The study of Geisner (20) confirms this and indicates that non-drinking students reported more depressive symptoms than drinking students. They state that drinking could be a strategy to cope with the experienced demands or a reason for enhancing social activities.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, social support is beneficial for dealing with stressful events and mental health problems (30) and therefore might influence the relationship between drinking behavior and mental health problems. However, either for social or coping reasons, excessive drinking behavior may lead to future mental health problems and other alcohol-related problems over time (20). Therefore, this finding emphasizes the importance of identifying students with excessive drinking behavior, providing insight into their health behavior and offering them guidance in effective coping strategies instead of drinking.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Psychological distress in general and symptoms of depression in particular, have been associated with lower academic achievement and detrimental health habits such as smoking and problem drinking among college students (Geisner, Mallett & Kilmer, 2012;Hysenbegasi, Hass, & Rowland, 2005;Kenney & Holahan, 2008;Mahmoud, Staten, Hall, & Lennie, 2012;Weitzman, 2004). Furthermore, physical illness and acute infectious illnesses have been associated with psychological distress in university students (Adams, Wharton, Quilter, & Hirsch, 2008;Rawson, Bloomer, & Kendall, 1994).…”
mentioning
confidence: 96%
“…[13,[17][18][19] It is also important to note that psychological distress, especially symptoms of depression, have been associated with lower academic achievement among university students and adverse health habits, such as poor eating and sleeping habits, smoking and problem drinking and acute infectious illnesses in students. [20][21][22][23][24][25][26] Taken together, these findings indicate the importance of assessing and addressing psychological distress related to stress in students with effective interventions and to reduce maladaptive coping behavior. [4] 3.…”
Section: The Problemmentioning
confidence: 99%